Categorias e mecanismos de resistência de genótipos de couve A Spodoptera frugiperda (J. E. Smith, 1797) (Lepidoptera: Noctuidae) - Moraes, Renato Franco Oliveira de [UNESP] (2014)
This work aimed to evaluate the resistance categories and mechanisms in kale genotypes to Spodoptera frugiperda (J. E. Smith, 1797). Experiments were conducted in the Departamento de Fitossanidade of Faculdade de Ciências Agrárias e Veterinárias, Campus de Jaboticabal, SP, Laboratório de Resistência de Plantas a Insetos, under environmental controlled conditions (27 ± 2 ºC temperature, 70 ± 10% R.H., and 12 hours photophase). In the feeding preference experiments, 25 genotypes were initially used, which were screened through free-choice and no-choice tests in a completely randomized design with 10 replications per treatment. The attractiveness was evaluated at 1; 5; 10; 15; 30; 60; 120; 360; 720; 1440 and 2880 minutes by counting larvae feeding on the genotypes, and at the end of the experiment the leaf area consumed was quantified. In addition, the hypothesis that the angle formed between the contact of the water drop and the leaf surface is related to the amount of epicuticular wax was tested, which may be an indicative of resistance and/or susceptibility. To evaluate the antibiosis, neonate larvae were individualized into Petri dishes and leaves of the five genotypes screened from the prior assays were provided to the larvae. The weight of 16 day-old larvae, weight of 24 hour-old pupae, duration of the larval and pupal periods, adult longevity, total viability and fecundity were recorded in two successive generations in a completely randomized design with 80 replications per treatment. Bromatological analysis was done to determine the nutritive value of the plants and the quantitative analysis of the secondary metabolite sinigrin and qualitative evaluation of several glucosinolates were also performed. In the antibiosis assay, in addition to the identification of the kale genotypes resistant to S. frugiperda, the levels of resistance were determined through multivariate analysis ...